Specters of western metaphysics - Roh, Hannah Amaris, author.
1 online resource
Keywords: "One of the first philosophical approaches to the study of Korea's ethnic nationalism, Christianity, the Sovereign Subject, and Ethnic Nationalism in Colonial Korea traces the impact of Christianity in the formation of Korean national identity, outlining the metaphysical origins of the concept of the sovereign subject. This monograph takes a meta-historical approach and engages the moral questions of Korean historiography amid the fraught politics of narrating colonialism and the postcolonial period. Indebted to Jacques Derrida's philosophy of deconstruction and his framework of "hauntology," this monograph unpacks the ethical consequences of ethnic nationalism, exploring how Western metaphysics has haunted imaginations of freedom in colonial Korea. While most studies of modern Korean nationalism and (post)colonialism have taken a cultural, literary, or social scientific approach, this book draws on the thought of Jacques Derrida to offer an innovative intellectual history of Korea's colonial period. By deconstructing the metaphysical claims of turn-of-the-century Protestant missionaries and early modern Korean intellectuals, the book showcases the relevance of Derrida's philosophical method in the study of modern Korean history. This is a must read for scholars interested in Derrida, historiography, and Korean history"--